Evaluation of the impact of inertia on system operation cost - Zhou, Lin; Wang, Hongliang; Wang, Yizheng; Zhang, Haipeng; Li, Wei; Li, Ran (Frontiers in Energy Research, 2023)
The inertia of the power system currently lies in a relatively narrow range. However, the increasing penetration of distributed energy resources (DERs) will significantly reduce the inertia level, meanwhile increasing its volatility. This will affect the system’s ability to contain the maximum frequency excursion and recover from large frequency disturbances. In order to maintain system frequency security and stability, a common practice is to incorporate frequency security constraints into the unit commitment (UC) model, so a concern is how the volume and volatility of system inertia impact system operation costs and energy clearing prices. Furthermore, inertia forecasting is often required when performing day-ahead UC with frequency security constraints. Therefore, this paper aims to evaluate the impact of system inertia on system operation costs and energy clearing prices. The experiment is designed under scenarios with different inertia volume, inertia volatility, and inertia forecasting errors. The results show that: 1) Increasing the system inertia volume can effectively reduce the system operation costs and energy clearing prices. 2) Increasing the inertia volatility will lead to an increase in system operation costs and energy clearing prices. 3) The increment of system operation cost caused by positive or negative errors of inertia forecasting is asymmetric.